1991
DOI: 10.1111/j.1471-4159.1991.tb11403.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Nicotinic Ligand Exposure on Functional Activity of Nicotinic Acetylcholine Receptors Expressed by Cells of the PC12 Rat Pheochromocytoma or the TE671/RD Human Clonal Line

Abstract: Studies were conducted to ascertain the temporal and dose-dependent effects of nicotinic ligand exposure on functional activity of different nicotinic acetylcholine receptor (nAChR) subtypes, as expressed by cells of the PC12 rat pheochromocytoma (ganglia-type nAChR) or the TE671/RD human (muscle-type nAChR) clonal line. Chronic (3-72-h) agonist (nicotine or carbamylcholine) treatment of cells led to a complete (TE671) or nearly complete (PC12) loss of functional nAChR responses, which is referred to as "funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 47 publications
4
50
0
Order By: Relevance
“…Previous reports indicated that one of the functional changes of up-regulated nAChRs is desensitization, which is confirmed by the electrophysiological method (15) and neurochemical measurement of 86 Rb ϩ efflux from cultured cells (14,62). On the other hand, our data presented here indicate that nicotine itself stimulates 45 Ca 2ϩ influx via up-regulated L-type VDCCs even after nnAChRs are up-regulated.…”
Section: Casupporting
confidence: 87%
“…Previous reports indicated that one of the functional changes of up-regulated nAChRs is desensitization, which is confirmed by the electrophysiological method (15) and neurochemical measurement of 86 Rb ϩ efflux from cultured cells (14,62). On the other hand, our data presented here indicate that nicotine itself stimulates 45 Ca 2ϩ influx via up-regulated L-type VDCCs even after nnAChRs are up-regulated.…”
Section: Casupporting
confidence: 87%
“…However, the time course and the extent to which nAChR properties are affected in various experimental preparations are still unclear (for reviews, see Gentry and Lukas 2002;Quick and Lester 2002). Depending on the experimental details (e.g., duration and timing of exposure), chronic activations can increase, decrease, or have no effect on nAChR expression and/or function (Rowell and Wonnacott 1990;Lukas 1991;Marks et al 1993;Peng et al 1994;Yu and Wecker 1994;Buisson and Bertrand 2001;Sokolova et al 2005). Here, we used a thick medullary slice preparation, which preserves nAChR location, density, number, and subtype composition, and tested whether DNE increases the magnitude of receptor desensitization and recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, membrane properties of nAChRs, especially activation and desensitization, have been extensively studied using receptors expressed at the neuromuscular junction (Colquhoun and Sakmann 1998;Fatt and Katz 1951;Galzi and Changeux 1995;Katz and Thesleff 1957) and in culture (Buisson and Bertrand 2001;Lukas 1991;Peng et al 1997;Sokolova et al 2005;Vallejo et al 2005). Despite their widespread presence in the CNS, much less is known about nAChR behavior in functionally viable brain tissue where the target neurons maintain their in vivo anatomical location, density, number, and subunit composition (but see Calabresi et al 1989;Guo and Lester 2007;Lester and Dani 1995;Wooltorton et al 2003).…”
mentioning
confidence: 99%
“…Under pathological conditions, such as the continuous presence of nicotine, receptors would be driven into these slowly reached irreversible (or long-lasting) inactive/desensitized conformations (Lukas, 1991;Marks et al, 1993;Peng et al, 1994)-a process likely influenced by the level of phosphorylation (Eilers et al, 1997;Gopalakrishnan et al, 1997). Occupancy of these deep desensitized states by nicotine could serve as the trigger for up-regulation in receptor number (Dani and Heinemann, 1996;Fenster et al, 1999b), shown to occur in vivo for ␣4␤2 nAChRs during chronic nicotine exposure (Marks et al, 1983;Schwartz and Kellar, 1985;Flores et al, 1992;Balfour, 1994); this again could potentially involve biochemical steps, because chronic nicotine promotes enhanced ␣4 subunit phosphorylation (Hsu et al, 1997).…”
Section: Regulation Of Desensitizationmentioning
confidence: 99%
“…After removal of agonist the receptor can recover back to its initial resting state; however, although desensitization is potentially fully reversible, complete recovery need not occur-particularly following chronic agonist treatment (Katz and Thesleff, 1957). Incomplete recovery may reflect long-lasting accumulation of receptors in one or more desensitized states or indeed may be due to the permanent loss of functional channels (Simasko et al, 1986;Boyd, 1987;Lukas, 1991; although see Buisson and Bertrand, 2002). Desensitization is qualitatively the same across all members of the nicotinic receptor family, and as such its essential behavior can be captured in a general model (see below) onto which any quantitative differences among individual nAChRs can be mapped.…”
mentioning
confidence: 99%